Recent advances on the one-pot synthesis to assemble size-controlled glycans and glycoconjugates and polysaccharides. (15th April 2021) - Xu, Han; Shen, Baoxing; Qiao, Meng; Linhardt, Robert J.; Zhang, Xing
Highlights: Homogeneous glycans are important for the development of carbohydrate-based drugs. One-pot synthesis represents the fastest strategy for glycan assembly. One-pot synthesis of glycans and oligosaccharides by chemical and enzymatic methods were discussed. Provides representative synthetic examples in detail. Abstract: Glycans and glycoconjugates in nature include macromolecules with important biological activities and widely distributed in all living organisms. These oligosaccharides and polysaccharides play important roles in a variety of normal physiological and pathological processes, such as cell metastasis, signal transduction, intercellular adhesion, inflammation, and immune response. However, the heterogeneity of naturally occurring glycans and glycoconjugates complicates detailed structure-activity relationship studies resulting in an incomplete understanding of their mechanisms of action and hindering further applications. Therefore, the synthesis of homogeneous, or nearly homogeneous, structurally defined glycans is of great significance for the development of carbohydrate-based drugs. One-pot synthesis represents the fastest strategy to assemble oligosaccharides and polysaccharides, although unfortunately, typically relies on random assembly. In this review, we examine the progress that has been made in the controlled one-pot synthesis of homogeneous or nearly homogeneous oligosaccharides and polysaccharides providing a broad spectrum of options to access size-controlled glycan products.